The Effectiveness of the Audiolingual Model Assisted by Podcast Media on the Listening Ability of Grade X Students at ESTV President Nicolau Lobato, Timor Leste - Abril da Conceicao; Suci Sundusiah; Ida Widia (Dinasti Publisher, 2025)
This study aims to test the effectiveness of the audiolingual model assisted by podcast media in improving the listening skills of grade X students at Estv President Nicolau Lobato, Timor Leste. This study's background is the EFL students' low listening ability caused by limited vocabulary, difficulty understanding native speaker speech, and the lack of authentic media in learning. The research method uses a quasi-experimental design with a pre-test–post-test control group model. The sample consists of two classes: the experimental group taught with the audiolingual model assisted by podcasts and the control group with conventional methods. The instrument, in the form of a listening test, was validated by experts and tested for reliability using the Cronbach's Alpha coefficient. Data analysis was carried out with descriptive statistics (mean, standard deviation) and inferential (paired sample t-test and independent sample t-test) at a significance level of 0.05. The results showed a significant improvement in the experimental group. The mean pre-test score of Instrument A (Greetings and Greetings) of 5.88 increased to 7.60 in the post-test (t = -19.34; p < 0.05), while Instrument B (Introductions) increased from 2.84 to 3.73 (t = -8.82; p < 0.05). The independent sample t-test results also showed a significant difference between the two instruments in the post-test (t = 22.13; p < 0.05). These findings support the behaviourist theory that emphasises the importance of drill and stimulus–response and the linguistic input theory that highlights the benefits of repeated exposure to authentic language. Thus, the combination of audiolingual and podcast models has been proven effective in improving listening skills while being relevant to the EFL context of developing countries.